1997
DOI: 10.1016/s0029-7844(97)89252-6
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Sleep, Mood, and Cognitive Function in Postpartum and Nonpostpartum Women

Abstract: Women must make important adjustments in their sleep patterns during the postpartum period. In the study group, these adjustments were largely successful, particularly after the first week postpartum, in avoiding the negative consequences of sleep disturbances such as dysphoric mood and impaired cognitive function. Nevertheless, the significant associations between sleep indices and mood and objective measures of cognitive function point to the importance of encouraging appropriate amounts of sleep for recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 30 publications
3
89
1
1
Order By: Relevance
“…The symptom profile was wide, as shown by numerous studies [6,[30][31][32][33][34][35][36][37][38]. Increased or decreased appetite, sleep disturbances, and decreased energy, each of which may be difficult to differentiate from healthy women because of postpartum status, other medical reasons and child care stress were also different [6][7][8]. Many of the symptoms are similar to those of generalised anxiety disorders, panic disorders, post-traumatic stress disorders, obsessive-compulsive disorders, and personality disorders, and co-morbidity may be high between these disorders and PPD [10,[13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptom profile was wide, as shown by numerous studies [6,[30][31][32][33][34][35][36][37][38]. Increased or decreased appetite, sleep disturbances, and decreased energy, each of which may be difficult to differentiate from healthy women because of postpartum status, other medical reasons and child care stress were also different [6][7][8]. Many of the symptoms are similar to those of generalised anxiety disorders, panic disorders, post-traumatic stress disorders, obsessive-compulsive disorders, and personality disorders, and co-morbidity may be high between these disorders and PPD [10,[13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of appetite, especially loss of appetite [6], fatigue, and disrupted sleep related to infant care may be difficult to distinguish from the symptoms of depression. Sleep disturbances can also lead to negative consequences, such as dysphoric mood and impaired cognitive function, while persistent difficulty with concentration or cognitive tasks is indicative of a mood disorder [7]. Substance abuse and medical causes of psychiatric symptoms, such as thyroid disorders, should also be considered [8].…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue reported by most women during the initial postpartum period is a major factor contributing to the onset of affect and mood disturbance. Swain and colleagues found that negative mood during the first postpartum week was mediated by the amount of time mothers spent awake at night [43], and fatigue has been shown to co-vary with scores on the Beck Depression Inventory during the first 2 postpartum weeks [44]. "Infant sleep problems" (reported by as many as 46% of parents) are associated with higher parental depression scores [45].…”
Section: Consequences Of Maternal Postpartum Sleep Disturbance For Mamentioning
confidence: 99%
“…Poor maternal sleep condition is thought to have a strong association to infant's sleep [9][10][11]. Sleep deprivation is associated with problematic sleepiness, fatigue, depressed mood, anxiety and poor daytime functioning [12].…”
Section: Introductionmentioning
confidence: 99%